2022
DOI: 10.3390/plants11030447
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phenolic Compounds and Antioxidant Activity in Plant Parts and Populations of Seven Underutilized Wild Achillea Species

Abstract: Evaluation of phytochemical composition of underutilized Achillea species provides the primary selection of germplasms with the desired quality of raw material for their further applications. The aim of the study was to evaluate the comprehensive distribution patterns of phenolic compounds in seven wild Achillea spp. and their plant parts, and to assess their antioxidant activity. Plant material was collected from different sites in Turkey. A complex of hydroxycinnamic acids, flavonols and flavones was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
2
9
1
Order By: Relevance
“…There is vast heterogeneity of phenolic compounds in plant species. Raudone et al ( 37 ) evaluated TPC content in 133 Indian medicinal plants in which they have found 1.8 mg GAE/g in M. oleifera seeds, which was quite lower than the present study (32.56 mg GAE/g). Another study conducted by Mwamatope et al ( 38 ) showed similar results (12.23 mg GAE/g) of TPC in ethanolic extract of M. oleifera leaves.…”
Section: Discussioncontrasting
confidence: 81%
“…There is vast heterogeneity of phenolic compounds in plant species. Raudone et al ( 37 ) evaluated TPC content in 133 Indian medicinal plants in which they have found 1.8 mg GAE/g in M. oleifera seeds, which was quite lower than the present study (32.56 mg GAE/g). Another study conducted by Mwamatope et al ( 38 ) showed similar results (12.23 mg GAE/g) of TPC in ethanolic extract of M. oleifera leaves.…”
Section: Discussioncontrasting
confidence: 81%
“…These compounds are deemed as active component of plants comprising good reducing potential due to which they act as good antioxidants. According to Raudone et al [25], phenolic and flavonoid contents present in Achillea wilhelmsii were among particularly important group of metabolites because they contribute to substantial biological activity and may be related to antioxidant potential. In current study, the total phenolic contents of WEEAW were 14:81 ± 0:18 mg GAE/g.…”
Section: Discussionmentioning
confidence: 99%
“…Identification was performed in a range of 200–400 nm wavelengths by comparing UV/Vis spectral data and retention times to those of standard compounds. Validation data of the method with representative chromatograms are provided in our previous paper [ 56 ].…”
Section: Methodsmentioning
confidence: 99%